PELATIHAN SURVEI KINERJA PENYEDIAAN AKSES INTERNET DI WILAYAH KERJA IV KOMINFO SURABAYA - Maulana Yusuf; Agung Satrio Wicaksono; Hamdan Akbar Notonegoro (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
This survey training was conducted with the aim of measuring the institutional performance of the Telecommunications and Information Accessibility Agency (BAKTI) Kominfo in Surabaya Work Area IV, covering five main provinces in Java, in carrying out the Universal Service Obligation (KPU) for Telecommunications and Informatics. The activity was designed to enhance the capability of the Area IV team to perform monitoring and evaluation (Monev) functions in accordance with regulatory mandates. The training methods focused on mastering techniques for mapping performance indicators, collecting, processing, and analyzing Universal Service Obligation data, including digital literacy. The results show the team's success in formulating policy scenarios and, most importantly, conducting a Large-Scale Field Survey to assess internet service provision performance across 441 points in Central Java, West Java, and Banten. With this new capability, the Area IV team successfully produced a comprehensive Final Survey Report, providing objective qualitative and quantitative information to measure BAKTI’s performance, thereby supporting strategic decision-making and enhancing the accountability of Universal Service Obligation programs in the region. Keywords: BAKTI Kominfo; Universal Service Obligation; the Institutional Performance; Monitoring dan Evaluasi; Survei